A questão da liberdade e da necessidade natural na Crítica da Razão Pura de Kant - Hosda, Everson Luiz Kunzler (2007)
The present research is inserted in the Line of Critical and Transcendental Philosophy Research of the Master‟s Degree Course in Philosophy, from the Post-Graduation Program in Philosophy, of the Federal University of Santa Maria UFSM. This dissertative study seeks to bring to discussion some questions that are in the genesis of the critical and transcendental philosophy of Kant. Among them the issue of the limits of the objective theoretical knowledge that is not about the increasing of science and that doesn‟t provide us not any new knowledge but makes us avoid the dogmatic illusion of intending to know objectively what is unattainable through experience. The purpose that guides this theoretical production concerns the investigation of Kant, in the solution of the Third Antinomy. It seeks to present how possible is the contradiction between a causality by freedom in relation to a causality by the laws of nature and, even if as problematic form in a theoretical perspective, a causality by freedom as a spontaneous cause on the determination of will. When Immanuel Kant (1724-1804) presents the second edition of his first critical work named Critical of Pure Reason (1787), the German philosopher is seeking to announce in his time the end of the theoretical obscurantism and the beginning of the search for the rational clarification of the foundations and possibilities of all human knowledge. This study deals with the investigation around the capacity of the human reason in its search to provide some kind of valid answer about till what point we can go ahead in the theoretical knowledge avoiding to fall in the simple affirmation without an objective foundation. Also, it seeks to understand, even if through a problematic point of view in a strictly theoretical perspective, the investigation of Kant (1787) that in his critical labor pursued to guarantee for the subsequent systematic of his works the possibility of a future critical theory of morality. To sum up, this study seeks to understand through a ystematic analysis of the Kantian philosophy presented in the work Critical of Pure Reason, specifically in the ranscendental Dialectic and in the Canon of the Pure Reason, the issue of freedom as long as a transcendental idea that can be thought without contradiction with the determinism of nature and that executes a necessary function for a speculative reason as long as a regulative idea. On the first Crítica, Kant doesn‟t show the objective reality of practical freedom. However, what the philosopher assures in this work through a purely practical use of reason, is the legitimate ambit for the morality in his philosophic system.